Implementasi Metode Average Akuntansi Dalam Membangun Sistem Informasi Inventory Menggunakan Framework Codeigniter - Vella Armi (Journal of Vocational Education and Information Technology (JVEIT), 2021)
The purpose of this study is the application of the Average Accounting method in building an inventory information system using a codeigniter framework to help warehouse managers of Bank Nagari Koto Baru Branch in completing inventory reports quickly and accurately. This research conducted a variety of problems, such as: data collection of available goods, supplier data collection, data collection of incoming goods, data collection of users, and data collection of goods used, then the data is processed into inventory reports using Microsoft Excel software. During the data collection process the warehouse manager must be careful to avoid data redundancy (double data) because the number of items to be recorded is very large. The system design in this study uses the Information Systems Flow (ASI) approach. The results of this study are an inventory information system by implementing the average accounting method using a codeigniter framework as a product that is very useful for the warehouse manager of Bank Nagari Koto Baru Branch to facilitate warehouse operations quickly, precisely, easily, accurately and produce quality inventory reports to help in decision making. This system is expected to be a very useful tool for managers in optimal warehouse operations.